Secondary battery and electronic device

CN119890399APending Publication Date: 2025-04-25NINGDE AMPEREX TECHNOLOGY LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510374900.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-04-25

Smart Images

  • Figure CN119890399A_ABST
    Figure CN119890399A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of energy storage, and particularly relates to a secondary battery and an electronic device. The secondary battery comprises an electrode assembly and a shell, wherein the shell is made of a steel shell; in the electrode assembly, a plurality of positive pole pieces and a plurality of negative pole pieces are alternately stacked, a diaphragm is arranged between the positive pole pieces and the negative pole pieces, the plurality of positive pole pieces comprise a first positive pole piece and a second positive pole piece, the compaction density of the first positive pole piece is A g / cm < 3 >, the compaction density of the second positive pole piece is B g / cm < 3 >, 3.3 < = A < = 4.3, 4.0 < = B < = 4.5, and B > A; the electrolyte comprises a cyano-containing compound shown in the formula I, the mass content of the compound shown in the formula I is X% based on the mass of the electrolyte, and X is larger than or equal to 1 and smaller than or equal to 7. By controlling the compaction density of the positive pole piece and cooperatively using the compound in the formula I in the electrolyte, the energy density and the cycle performance of the battery can be effectively balanced, and the stability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of energy storage technology, and specifically relates to a secondary battery and an electronic device. Background Art

[0002] Secondary batteries are a type of energy storage device based on reversible electrochemical reactions that can achieve multiple charge and discharge cycles through external electrical energy input. They have high energy density, long cycle life and environmental protection advantages, and are increasingly widely used.

[0003] Steel shell is a common shell for secondary batteries. It has high rigidity but poor elastic deformation ability. Increasing the compaction density of secondary battery pole pieces can effectively increase the energy density of the battery. When the secondary battery is charged and discharged, the pole pieces will expand due to charging and discharging. The greater the compaction density, the greater the expansion stress. The generated expansion stress cannot be released through the deformation of the shell, but is transferred to the weak parts of the structure, resulting in overall buckling or bulging of the steel shell, internal short circuit of the battery and other problems, affecting the safe use of the battery. Therefore, improving the stability of the battery without affecting the battery performance has become an urgent problem to be solved in the application of secondary batteries. Summary of the invention

[0004] In view of this, the present application provides a secondary battery and an electronic device, which can effectively balance the energy density and stability of the battery by controlling the compaction density of the positive electrode plate and using the compound of formula I in the electrolyte.

[0005] In the first aspect, the present application provides a secondary battery, including an electrode assembly and a shell, wherein the shell is made of a steel shell; the electrode assembly includes an electrolyte, a positive electrode sheet, a negative electrode sheet, and a separator, wherein a plurality of positive electrode sheets and a plurality of negative electrode sheets are alternately stacked, and the separator is arranged between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet includes a first positive electrode sheet and a second positive electrode sheet, and the compaction density of the first positive electrode sheet is A g / cm 3 The compaction density of the second positive electrode sheet is B g / cm 3 , 3.3≤A≤4.3, 4.0≤B≤4.5, B>A; the electrolyte includes a compound of formula I, the compound of formula I contains a cyano group, and the mass content of the compound of formula I is X%, 1≤X≤7 based on the mass of the electrolyte. By controlling the compaction density of the positive electrode sheet and using the compound of formula I in the electrolyte, a secondary battery with a high energy density can be stably used after multiple charges and discharges, effectively balancing the energy density and stability of the battery.

[0006] In some preferred embodiments, 3.5≤A≤4.2, 4.1≤B≤4.4; and / or 1.5≤X≤6. By further optimizing the compaction density of the positive electrode sheet and the compound of formula I, the energy density and stability of the battery can be better balanced.

[0007] In some embodiments, the first positive electrode plate includes a first positive electrode collector and a first positive electrode active material layer disposed on at least one surface of the first positive electrode collector, the thickness of the first positive electrode active material layer is a μm, 25≤a≤90; and / or, the second positive electrode plate includes a second positive electrode collector and a second positive electrode active material layer disposed on at least one surface of the second positive electrode collector, the thickness of the second positive electrode active material layer is b μm, 25≤b≤90.

[0008] In some preferred embodiments, 30≤a≤75; and / or, 30≤b≤75.

[0009] The positive electrode active material layer within the above thickness range has a larger active material load per unit area, so that the battery has a higher capacity and energy density, while not being prone to cracking or aggravating concentration polarization due to the active material layer being too thick, thereby achieving a balance between energy density, cost and cycle performance.

[0010] In some embodiments, the compound of formula I includes at least one of the following compounds: Formula I-1, Formula I-2, Formula I-3, Formula I-4, Formula I-5, Formula I-6, Formula I-7, Formula I-8, Formula I-9.

[0011] Adding the above compounds to the electrolyte can effectively inhibit the decomposition and gas production of the electrolyte, reduce the risk of bulging and leakage, and comprehensively enhance the various properties of the electrolyte.

[0012] In some embodiments, the positive electrode plate includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material includes at least one of lithium cobalt oxide and nickel cobalt manganese oxide. The above oxides have high lithium ion insertion and extraction efficiency and excellent volume energy density.

[0013] In some embodiments, the first positive electrode active material layer includes a first material layer and a second material layer, and the first material layer is disposed between the first positive electrode current collector and the second material layer; and / or, the second positive electrode active material layer includes a third material layer and a fourth material layer, and the third material layer is disposed between the second positive electrode current collector and the fourth material layer; wherein the thicknesses of the first material layer, the second material layer, the third material layer, and the fourth material layer are respectively a1μm, a2μm, b1μm, and b2μm, and: 15≤a1≤80; 10≤a2≤75; 15≤b1≤80; 10≤b2≤75. Through the above design, including but not limited to using different types or contents of active materials and binders in the active material layer, or using different coating methods, etc., the comprehensive performance of the battery can be effectively improved.

[0014] In some embodiments, the electrolyte further includes at least one of the following additives: ethyl difluoroacetate, difluoroethyl acetate, ethyl monofluoroacetate, monofluoroethyl acetate, ethyl trifluoroacetate, trifluoroethyl acetate, methyl difluoroacetate, methyl monofluoroacetate, monofluoromethyl acetate, methyl trifluoroacetate, propyl difluoroacetate; based on the mass of the electrolyte, the mass content of the additive is Y%, 10≤Y≤40, 0.025≤X / Y≤0.7. The above additives can form a stable and dense solid electrolyte interface (SEI) rich in lithium fluoride on the surface of the negative electrode, inhibit further reaction of lithium metal and solvent, reduce the interfacial impedance of the battery, improve the transmission efficiency of lithium ions at the electrode / electrolyte interface, and improve various performances of the battery.

[0015] In a second aspect, the present application provides an electronic device, comprising the secondary battery described in any one of the first aspects.

[0016] The beneficial effects of this application are as follows: The present application provides a secondary battery, including an electrolyte, an electrode assembly and a shell, wherein the shell is made of a steel shell; the electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator, wherein a plurality of positive electrode sheets and a plurality of negative electrode sheets are alternately stacked, and the separator is arranged between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet includes a first positive electrode sheet and a second positive electrode sheet, and the compaction density of the first positive electrode sheet is A g / cm 3 The compaction density of the second positive electrode sheet is B g / cm 3, 3.3≤A≤4.3, 4.0≤B≤4.5, B>A; the electrolyte includes a compound of formula I, the compound of formula I contains a cyano group, and based on the mass of the electrolyte, the mass content of the compound of formula I is X%, and 1≤X≤7. In the present application, by designing the first positive electrode plate and the second positive electrode plate to have different compaction densities, a smaller compaction density is set in the area with larger expansion stress, and a larger compaction density is set in the area with smaller expansion stress, so that the battery can have a higher energy density and effectively avoid deformation of the steel shell battery structure and short circuit of the battery; the compound of formula I has a high oxidation potential and is preferentially stable on the surface of the high-voltage positive electrode. When the content of the compound of formula I is within the above range, it can form a nitrile protective film with excellent performance on the surface of the positive electrode, stabilize the active metal in the positive electrode active material, inhibit the dissolution of the active metal, reduce the oxygen release reaction, effectively inhibit gas production, and reduce the risk of battery bulging and leakage. The present application controls the compaction density of the positive electrode sheet and uses the compound of formula I in the electrolyte, so that a secondary battery with a higher energy density can still be used stably after multiple charge and discharge cycles, effectively balancing the energy density and stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A schematic cross-sectional view of a secondary battery according to an embodiment of the present application in the thickness direction of an electrode assembly; Figure 2 for Figure 1 The enlarged schematic diagram of point A in the middle; Figure 3 A schematic cross-sectional view of a secondary battery according to another embodiment of the present application in the thickness direction of an electrode assembly; Figure 4 for Figure 3 A magnified schematic diagram of point B in the middle.

[0018] Reference numerals: 1-electrode assembly; 11-positive electrode plate; 111-first positive electrode plate; 112-second positive electrode plate; 12-diaphragm; 13-negative electrode plate; 2-shell. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0020] In this application, the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inside", "outside", "vertical", "horizontal", "lateral", "longitudinal" and the like indicate positions or positional relationships based on the positions and positional relationships shown in the drawings or the positions or positional relationships in which the products of this application are usually placed when used. These terms are mainly used to better describe this application and its embodiments, and are not used to limit the indicated devices, elements or components to have specific positions, or to be constructed and operated in specific positions.

[0021] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those of ordinary skill in the art, the specific meanings of these terms in this application can be understood according to specific circumstances.

[0022] In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.

[0023] It should be noted that, in the content of the present application, lithium-ion batteries are used as an example of batteries to explain the present application, but the batteries of the present application are not limited to lithium-ion batteries.

[0024] Steel shell battery refers to a type of battery with a steel shell as the shell. The steel shell has a high yield strength, generally not less than 300MPa, and can withstand external puncture and extrusion. The shell is not easy to deform during the battery cycle. In addition, the steel shell has the advantages of strong sealing, high corrosion resistance and low cost, so it has a wide range of application prospects. However, the rigidity of the steel shell also makes it impossible to release stress through deformation. Steel shell batteries mostly use a laminated or winding structure, and the pole piece is tightly wrapped. When the pole piece expands, it is limited by the rigidity of the shell, and the expansion force will be transmitted to the inner wall of the steel shell through the pole piece layer, forming a "sandwich effect" and aggravating local bulging. Under high pressure or high temperature, the electrolyte is easily oxidized and decomposed to produce gases such as CO2 and CH4, and the strong sealing of the steel shell will cause the internal pressure of the battery to accumulate rapidly. If the expansion force and the internal pressure of the battery are too large, and the gas cannot be discharged, it will cause problems such as overall buckling or bulging of the steel shell and internal short circuit of the battery, affecting the safe use of the battery. The inventors have found that in order to increase the energy density of the battery, the compaction density of the positive electrode of the battery is usually high, and the high compaction density means low porosity, lack of buffering during expansion, and stress is more easily transmitted to the steel shell to cause deformation. The positive electrode relatively close to the steel shell may allow partial volume changes due to the presence of tiny gaps, while the positive electrode relatively close to the inside of the battery cell is usually subject to stronger mechanical constraints, which makes it more difficult to release the stress generated during expansion, resulting in battery bulging. In this case, the positive electrode particles are more likely to produce microcracks, accelerating the battery capacity decay. In addition, high compaction density will aggravate battery side reactions, and higher current density may cause local overcharging, leading to oxidative decomposition (gas production) of the electrolyte and dissolution of transition metal ions, further promoting expansion, affecting the stable use of the battery, and creating safety hazards.

[0025] Based on this, the present application provides a secondary battery, including an electrode assembly 1 and a shell 2, wherein the shell 2 is made of a steel shell; the electrode assembly 1 includes an electrolyte, a positive electrode sheet 11, a negative electrode sheet 13, and a separator 12, wherein a plurality of positive electrode sheets 11 and a plurality of negative electrode sheets 13 are alternately stacked, and the separator 12 is arranged between the positive electrode sheets 11 and the negative electrode sheets 13. Among them, the positive electrode sheet 11 includes a first positive electrode sheet 111 and a second positive electrode sheet 112, and the compaction density of the first positive electrode sheet 111 is A g / cm 3 The compaction density of the second positive electrode sheet 112 is B g / cm 3 , 3.3≤A≤4.3, 4.0≤B≤4.5, B>A; the electrolyte comprises a compound of formula I, the compound of formula I contains a cyano group, and the mass content of the compound of formula I is X%, based on the mass of the electrolyte, and 1≤X≤7.

[0026] Illustratively, the value of A can be 3.3, 3.4, 3.6, 3.9, 4.0, 4.1, 4.3, or a range consisting of any two of the above values; the value of B can be 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, or a range consisting of any two of the above values; the value of X can be 1, 2, 3, 4, 5, 6, 7, or a range consisting of any two of the above values.

[0027] Please also refer to Figure 1~Figure 4 In the present application, the first positive electrode sheet 111 refers to the positive electrode sheet 11 that is relatively far away from the shell 2 in the thickness direction of the electrode assembly, that is, relatively close to the inside of the electrode assembly, and the second positive electrode sheet 112 refers to the positive electrode sheet 11 that is relatively close to the shell 2 in the thickness direction of the electrode assembly. When the number of positive electrode sheets 11 is odd, the first positive electrode sheet 111 refers to 1 to 5 positive electrode sheets that are relatively close to the inside of the battery cell, that is, the first positive electrode sheet 111 can be 1, 2, 3, 4, 5, or 5 at most; when the number of electrode sheets is even, the first positive electrode sheet 111 refers to 1 to 6 positive electrode sheets that are relatively close to the inside of the battery cell, that is, the first positive electrode sheet 111 can be 1, 2, 3, 4, 5, or 6, or 6 at most. In the present application, the first positive electrode sheet 111 and the second positive electrode sheet 112 are designed to have different compaction densities. Specifically, the first positive electrode sheet 111, which is subject to greater mechanical constraints, has a smaller compaction density, thereby reducing the expansion stress of the first positive electrode sheet area; and the compaction density of the second positive electrode sheet 112, which is relatively close to the shell 2, is relatively large, ensuring the energy density of the battery. Through the above design, the battery can have a higher energy density, while effectively avoiding the deformation of the battery structure of the shell 2 and the short circuit of the battery; the compound of formula I has a high oxidation potential, and is preferentially stable on the surface of the high-voltage positive electrode. When the content of the compound of formula I is within the above range, it can form a nitrile protective film with excellent performance on the surface of the positive electrode, stabilize the active metals in the positive electrode active material, inhibit the dissolution of the active metals, reduce the oxygen release reaction, effectively inhibit gas production, and further reduce the risk of battery bulging and leakage. In the present application, by controlling the compaction density of the positive electrode sheet 11 and the use of the compound of formula I in the electrolyte, the secondary battery with higher energy density can still be used stably after multiple charging and discharging, effectively balancing the energy density and stability of the battery.

[0028] In some preferred embodiments, 3.5≤A≤4.2, 4.1≤B≤4.4; 1.5≤X≤6. By further optimizing the compaction density of the positive electrode sheet 11 and the compound of formula I, the values ​​of A, B, and X are controlled within the above atmosphere, which can better balance the energy density and stability of the battery. Exemplarily, the value of A can be 3.5, 3.6, 3.8, 3.9, 4.0, 4.2, or a range consisting of any two of the above values; the value of B can be 4.1, 4.2, 4.3, 4.4, or a range consisting of any two of the above values; the value of X can be 1.5, 2, 3.5, 4, 5, 5.5, 6, or a range consisting of any two of the above values.

[0029] In some embodiments, the first positive electrode plate 111 includes a first positive electrode current collector and a first positive electrode active material layer disposed on at least one surface of the first positive electrode current collector, and the thickness of the first positive electrode active material layer is a μm, 25≤a≤90; and / or, the second positive electrode plate 112 includes a second positive electrode current collector and a second positive electrode active material layer disposed on at least one surface of the second positive electrode current collector, and the thickness of the second positive electrode active material layer is b μm, 25≤b≤90. Exemplarily, the value of a may be 25, 30, 40, 46, 55, 67, 72, 78, 80, 90, or a range consisting of any two of the above values; the value of b may be 25, 33, 48, 57, 62, 73, 82, 90, or a range consisting of any two of the above values.

[0030] In some preferred embodiments, 30≤a≤75; and / or, 30≤b≤75. For example, the value of a can be 30, 42, 50, 53, 66, 75, or a range consisting of any two of the above values; the value of b can be 30, 36, 42, 55, 60, 75, or a range consisting of any two of the above values.

[0031] The value of a can be the same as or different from that of b. The above “arranged on at least one surface of the first (second) positive electrode current collector” means that the positive electrode active material layer can be located on one surface of the positive electrode current collector along its own thickness direction, or on two surfaces of the positive electrode current collector along its own thickness direction. It should be noted that the “surface” here can be the entire area of ​​the surface of the positive electrode current collector, or it can be a partial area of ​​the surface of the positive electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved.

[0032] The positive electrode active material layer needs to have a certain thickness to accommodate more active substances and improve the battery capacity and energy density. Controlling the thickness of the positive electrode active material layer within the range described in this application can, on the one hand, alleviate the battery concentration polarization when the thickness is too thick, increase the battery capacity utilization rate, reduce the volume change of the positive electrode during charging and discharging, and slow down the battery expansion; on the other hand, the positive electrode material layer of a certain thickness in this application can ensure the content of the active substance and make the positive electrode plate 11 have a certain stability, achieving a balance between energy density, cost and cycle performance.

[0033] In some embodiments, the compound of formula I includes at least one of the following compounds: Formula I-1, Formula I-2, Formula I-3, Formula I-4, Formula I-5, Formula I-6, Formula I-7, Formula I-8, Formula I-9.

[0034] The above-mentioned compound of formula I has a high oxidation potential, is preferentially stable on the surface of the high-voltage positive electrode, can effectively inhibit the oxidation decomposition of the electrolyte, capture the active free radicals generated by the decomposition of the electrolyte, block the chain reaction, and reduce gas production; at the same time, the above-mentioned compound can be oxidized on the surface of the positive electrode to generate nitrogen-containing compounds, forming a dense and ion-conductive interface film, inhibiting the dissolution of transition metals, reducing the catalytic gas production of the electrolyte and the formation of dendrites. Adding the above-mentioned compound to the electrolyte can effectively inhibit the decomposition and gas production of the electrolyte, reduce the risk of bulging and leakage, and comprehensively enhance the various properties of the electrolyte.

[0035] In some embodiments, the positive electrode plate 11 includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material includes at least one of lithium cobalt oxide and nickel cobalt manganese oxide. Lithium cobalt oxide and nickel cobalt manganese oxide have a layered structure, high lithium ion extraction efficiency, and excellent volume energy density. By adjusting the content ratio of each element in the oxide, the various performances of the battery can be further optimized. It should be noted that the positive electrode active material in this application includes doped and coated modified positive electrode active materials.

[0036] In some embodiments, the first positive electrode active material layer includes a first material layer and a second material layer, and the first material layer is disposed between the first positive electrode current collector and the second material layer; and / or, the second positive electrode active material layer includes a third material layer and a fourth material layer, and the third material layer is disposed between the second positive electrode current collector and the fourth material layer; wherein the thicknesses of the first material layer, the second material layer, the third material layer, and the fourth material layer are respectively a1μm, a2μm, b1μm, and b2μm, and: 15≤a1≤80; 10≤a2≤75; 15≤b1≤80; 10≤b2≤75. In addition to the above-mentioned first material layer and second material layer, the positive electrode active material layer also includes a primer, that is, a layer of functional material is pre-coated on the surface of the positive electrode current collector, including but not limited to conductive carbon material, metal oxide, etc. By using different types or contents of active materials and binders in the active material layer, or adopting different coating methods, coating thicknesses, etc., the stability and various properties of the active material layer can be further enhanced, and the comprehensive performance of the battery can be effectively improved.

[0037] In some embodiments, the electrolyte further includes at least one of the following solvents: ethyl difluoroacetate, difluoroethyl acetate, ethyl monofluoroacetate, monofluoroethyl acetate, ethyl trifluoroacetate, trifluoroethyl acetate, methyl difluoroacetate, methyl monofluoroacetate, monofluoromethyl acetate, methyl trifluoroacetate, propyl difluoroacetate; based on the mass of the electrolyte, the mass content of the additive is Y%, 10≤Y≤40, 0.025≤X / Y≤0.7. The above additives can form a stable and dense solid electrolyte interface film (SEI) rich in lithium fluoride on the surface of the negative electrode, inhibit further reaction of lithium metal with the solvent, reduce the interfacial impedance of the battery, and improve the transmission efficiency of lithium ions at the electrode / electrolyte interface. The compound of formula I in the present application is used in combination with the above compound to achieve optimization of the division of labor at the positive and negative electrode interfaces and synergistic inhibition of side reactions, thereby improving the various performances of the battery.

[0038] The present application has no particular restrictions on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the positive electrode current collector may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector). The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate.

[0039] In the present application, the positive electrode active material layer may further include a positive electrode binder and a positive electrode conductor. The present application does not particularly limit the type of positive electrode binder in the positive electrode active material layer, as long as the purpose of the present application can be achieved. For example, the positive electrode binder may include but is not limited to polyvinylidene fluoride, polytetrafluoroethylene, polyolefins, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, modified polyvinylidene fluoride, modified styrene-butadiene rubber (SBR) or at least one of polyurethane. In some embodiments, the polyolefin binder includes at least one of polyethylene, polypropylene, polyolefin ester, polyolefin alcohol or polyacrylic acid.

[0040] The present application has no particular restrictions on the type of positive electrode conductive agent in the positive electrode active material layer, as long as the purpose of the present application can be achieved. In some embodiments, the positive electrode conductive agent includes carbon-based materials, such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black or carbon fiber; metal-based materials, such as metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers, such as polyphenylene derivatives; or mixtures thereof. The present application has no particular restrictions on the mass ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder in the positive electrode active material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. For example, the loading amount of the positive electrode active material in the positive electrode sheet is 4.0 mg / cm 2 Up to 10.0 mg / cm 2 .

[0041] In the present application, the secondary battery also includes a negative electrode plate, and the negative electrode plate includes a negative electrode current collector and a negative electrode material layer arranged on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer arranged on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be arranged on one surface of the negative electrode current collector along its own thickness direction, or it can be arranged on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the negative electrode current collector or a partial area of ​​the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved. This application has no special restrictions on the negative electrode current collector, as long as the purpose of this application can be achieved. For example, it can include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector, etc.

[0042] The negative electrode material layer of the present application includes a negative electrode active material. The present application has no particular limitation on the negative electrode active material, as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO X (0.5<x<1.6), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structure lithium titanate Li4Ti5O12 , Li-Al alloy or metallic lithium, etc.

[0043] The negative electrode material layer of the present application also includes a binder. The present application has no special restrictions on the binder in the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the binder can be at least one of the above-mentioned binders. The negative electrode material layer of the present application also includes a conductive agent. The present application has no special restrictions on the conductive agent in the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the conductive agent can be at least one of the above-mentioned conductive agents. The present application has no special restrictions on the mass ratio of the negative electrode active material, the binder, and the conductive agent in the negative electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.

[0044] The present application has no particular limitation on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness of the negative electrode current collector is 5 μm to 16 μm. The present application has no particular limitation on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved, for example, the thickness of the single-sided negative electrode material layer is 30 μm to 120 μm.

[0045] In the present application, the secondary battery also includes a diaphragm, which is used to separate the positive electrode plate and the negative electrode plate, prevent the internal short circuit of the secondary battery, allow the electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process. The present application has no special restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters [for example, polyethylene terephthalate (PET) film], cellulose, polyimide (PI), polyamide (PA), spandex or aramid; the type of diaphragm may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.

[0046] In the present application, the diaphragm may include a substrate and a surface treatment layer. The substrate may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a binder, and the present application has no particular restrictions on the above-mentioned inorganic particles, for example, it may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the above-mentioned binder, for example, it may be at least one of the aforementioned binders. The polymer layer contains a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).

[0047] The secondary battery in the present application also includes a tab, which can lead the current out of the electrode assembly. The tab may include a positive tab and a negative tab, which are connected to the positive current collector substrate and the negative current collector substrate respectively. The tab may be formed by cutting or trimming the current collector substrate, or may be connected by welding. The present application does not limit the number, position, formation method, etc. of the tab.

[0048] The present application does not particularly limit the type of secondary battery, which may include any device that generates an electrochemical reaction. In the present application, the secondary battery may include, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery or a lithium ion polymer secondary battery (lithium ion polymer battery), etc.

[0049] The preparation process of the secondary battery of the present application is well known to those skilled in the art, including but not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of the stacked structure, placing the electrode assembly in a housing, injecting the electrolyte into the housing and sealing it to obtain a secondary battery. In addition, overcurrent protection elements, guide plates, etc. can also be placed in the housing as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging.

[0050] In a second aspect, the present application provides an electronic device, comprising the secondary battery described in any of the aforementioned schemes.

[0051] The electronic device of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. For example, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor.

[0052] The following is an example of a lithium-ion battery and the scheme of the present application is described in conjunction with the following specific examples. Unless otherwise specified, the raw materials used in the following examples are all from ordinary commercially available products, and the devices or equipment used are all purchased from conventional market sales channels. Various tests and evaluations are carried out according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0053] Test methods and equipment: Compaction density test: Take a lithium-ion battery, place it in a constant temperature test box at 25℃, let it stand for 30 minutes, charge it to 4.5V at a constant current of 0.5C, then charge it to a current of 0.025C at the 4.5V constant voltage, let it stand for 5 minutes, discharge it to 2.8V at a constant current of 0.5C; then charge it to 50% SOC at a constant current of 0.5C, remove the negative electrode plate, weigh the weight and plate thickness, and calculate the compaction density of the negative electrode plate according to ρ=m / V.

[0054] Energy density test: Place the lithium-ion battery in a 25°C constant temperature environment and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature of 25°C. Charge at 0.5C constant current to 4.5V, charge at 4.5V constant voltage to a current of 0.05C, let it stand for 5 minutes; discharge at 0.2C constant current to 3.0V; let it stand for 5 minutes, and the test is over. Record the discharge capacity at 0.2C constant current discharge as C, the discharge platform voltage as P, measure the lithium-ion battery thickness as G, the lithium-ion battery length as L, and the lithium-ion battery width as W, then the volume energy density E of the lithium-ion battery can be calculated according to the following formula: E = (C×P) / (G×L×W).

[0055] Cycle performance test: Place the lithium-ion battery in a 25°C constant temperature environment and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature of 25°C. Charge it to 4.5V at a constant current of 0.5C, charge it to a current of 0.025C at a constant voltage of 4.5V, let it stand for 5 minutes, and discharge it to 3.0V at a constant current of 0.5C. Record the initial discharge capacity as C0. Cycle the above charge and discharge steps for 500 cycles, and record the discharge capacity after 500 cycles as C1.

[0056] Cycle capacity retention rate = C1 / C0×100%.

[0057] Example 1-1 <Preparation of Electrolyte> In a dry argon atmosphere glove box, lithium hexafluorophosphate was dissolved in a solution containing a compound of formula I (adiponitrile) and propylene carbonate (basic solvent). Based on the mass of the electrolyte, the mass content of lithium hexafluorophosphate was 12.5%, the mass content of adiponitrile was 4%, and the balance was propylene carbonate (basic solvent).

[0058] <Preparation of positive electrode sheet> The positive electrode active material lithium cobalt oxide (LiCoO2), the positive electrode binder polyvinylidene fluoride (PVDF), and the positive electrode conductive agent Super P are mixed in a mass ratio of 97:1.6:1.4, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 75wt%, and stirred evenly. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and dried at 110°C to obtain a positive electrode sheet coated with a single-sided positive electrode active material. After that, the above steps are repeated on the other surface of the positive electrode sheet to obtain a positive electrode sheet coated with a double-sided positive electrode active material. After the coating is completed, the positive electrode sheet is cold pressed under rollers with different pressures to a fixed compaction density sheet, and cut into a positive electrode sheet with a specification of 39 mm×58 mm for standby use.

[0059] <Preparation of negative electrode sheet> The negative electrode active material artificial graphite, negative electrode conductive agent Super P, thickener sodium carboxymethyl cellulose (CMC), and negative electrode binder styrene butadiene rubber (SBR) were mixed in a mass ratio of 96.4:1.5:0.5:1.6, and then deionized water was added as a solvent to prepare a negative electrode slurry with a solid content of 30wt%. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 10 µm, and dried at 110°C to obtain a negative electrode sheet coated with a negative electrode active material layer on one side, and then the above steps were repeated on the other surface of the negative electrode sheet to obtain a negative electrode sheet coated with a negative electrode active material layer on both sides. After coating, the negative electrode sheet was cold pressed and cut into negative electrode sheets with a specification of 41 mm×61 mm for standby use.

[0060] <Diaphragm> A polyethylene-polypropylene film with a thickness of 7 μm was used.

[0061] <Preparation of lithium-ion batteries> The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is located between the positive electrode sheet and the negative electrode sheet to play a barrier role, and the electrode assembly is stacked. After welding the pole ear, the electrode assembly is placed in a steel shell, placed in a vacuum oven at 85°C for 12 hours to remove moisture, and the prepared electrolyte is injected. After vacuum packaging, standing, formation and other processes, a lithium-ion battery is obtained.

[0062] Example 1-2 to Example 1-16, Comparative Example 1-1 to Comparative Example 1-5 The difference from Example 1-1 is that the parameters are adjusted according to Table 1. The performance test results of each embodiment and comparative example are shown in Table 1.

[0063] Table 1

[0064] As shown in Table 1, the present application designs the positive electrode sheet to include a compaction density of 3.3 g / cm 3 ~4.3g / cm 3 The first positive electrode sheet has a compaction density of 4.0 g / cm 3 ~4.5g / cm 3 The second positive electrode sheet is provided, and the compaction density of the first positive electrode sheet is less than that of the second positive electrode sheet. The electrolyte includes a compound of formula I containing a cyano group, and the mass content of the compound of formula I is 1% to 7%. The lithium ion battery can have both a higher energy density and a higher cycle capacity retention rate, thereby effectively balancing the energy density and stability of the battery.

[0065] Referring to Examples 1-1 to 1-5, Comparative Examples 1-4 and 1-5, it can be seen that the compaction density of the first positive electrode sheet is 3.8 g / cm 3 The compaction density of the second positive electrode sheet is 4.3g / cm 3 When the compound of formula I is adiponitrile, as the mass content of the compound of formula I gradually increases from 1% to 6%, the energy density of the lithium ion battery remains unchanged, and the cycle capacity retention rate increases from 60% to 73%; when the mass content of the compound of formula I increases to 7%, the cycle capacity retention rate of the lithium ion battery decreases to 55%; when the mass content of the compound of formula I increases to 8%, that is, when it exceeds the upper limit of the range described in the present application, the cycle capacity retention rate of the lithium ion battery significantly decreases to 43%; and when the mass content of the compound of formula I is 0.5%, that is, when it exceeds the lower limit of the range described in the present application, the cycle capacity retention rate of the lithium ion battery is 40%, and the stability is poor.

[0066] In summary, when the compaction density of the positive electrode sheet is within the range described in the present application, and the mass content of the compound of formula I is between 1% and 7%, especially between 1.5% and 6%, the lithium-ion battery has a higher cycle capacity retention rate and better stability.

[0067] In addition to the content of the compound of formula I, the type of the compound of formula I also affects the stability of the lithium ion battery. From Examples 1-12 to 1-16, it can be seen that by adding the compound of formula I described in the present application to the electrolyte, the lithium ion battery has a higher cycle capacity retention rate and better stability.

[0068] Referring to Examples 1-6 to 1-11, when the compound of Formula I is adiponitrile and the mass content is 4%, the compaction density of the first positive electrode sheet is 3.3 g / cm 3 ~4.3g / cm 3 Change, the compaction density of the second positive electrode sheet is 4.0g / cm 3 ~4.5g / cm 3 The energy density of lithium-ion batteries increased from 521Wh / L to 632Wh / L, but a higher energy density does not necessarily correspond to a higher cycle capacity retention rate. The compaction density of the first and second pole pieces is 3.5g / cm 3 4.4g / cm 3 When the energy density of the lithium-ion battery is 540Wh / L, the cycle capacity retention rate is high, which is 78%; while the compaction density of the first and second pole pieces is 4.3g / cm 3 , 4.5g / cm 3 When the energy density of the lithium-ion battery is 632Wh / L, the cycle capacity retention rate drops to 63%. Further, referring to Comparative Example 1-2, the compaction density of the first pole piece and the second pole piece is 4.3g / cm 3 , 5.0g / cm 3 When the upper limit of the range described in the present application is exceeded, although the energy density is high, the cycle capacity retention rate of the lithium ion battery is reduced to 32%, and the battery stability is significantly reduced; in Comparative Example 1-1, the compaction density of the first positive electrode sheet and the second positive electrode sheet is 3.0 g / cm 3 When the lower limit of the range described in this application is exceeded, the energy density of the lithium-ion battery is 463Wh / L, and the cycle capacity retention rate is 54%, both of which are worse than the performance when the compaction density is within the range described in this application.

[0069] Further, referring to Comparative Examples 1-3, although the compaction density of the first positive electrode sheet and the second positive electrode sheet are both within the range described in the present application, the compaction density of the first positive electrode sheet is greater than that of the second positive electrode sheet, and the cycle capacity retention rate of the lithium-ion battery is a relatively low 35%. It can be seen that controlling the compaction density of the first positive electrode sheet to be less than that of the second positive electrode sheet has a significant improvement in the stability of the lithium-ion battery.

[0070] In summary, the compaction density of the first positive electrode sheet is 3.3g / cm 3 ~4.3g / cm 3 , the compaction density of the second positive electrode sheet is 4.0g / cm 3 ~4.5g / cm 3 In particular, the first positive electrode sheet has a compaction density of 3.5 g / cm 3 ~4.2g / cm 3 The compaction density of the second positive electrode sheet is 4.1g / cm 3 ~4.4g / cm 3 When the compaction density of the first positive electrode sheet is controlled to be less than that of the second positive electrode sheet, and the type and content of the compound of formula I are within the scope of the present application, the energy density and cycle capacity retention rate of the lithium-ion battery can be high, thereby achieving a balance between energy density and stability.

[0071] Example 2-1 to Example 2-10 The difference from Example 1-1 is that the thickness of the positive electrode active material layer is adjusted according to the parameters shown in Table 2. The performance test results of each embodiment and comparative example are shown in Table 2.

[0072] Table 2

[0073] As can be seen from Table 2, in Examples 2-1 to 2-8, when the thickness of the first positive electrode active material layer and the second positive electrode active material layer is controlled at 25μm~90μm, especially 30μm~75μm, the energy density and cycle capacity retention rate of the lithium ion battery are both high. In Example 2-9, the thickness of the first positive electrode active material layer and the thickness of the second positive electrode active material layer are thinner, and the cycle capacity retention rate of the lithium ion battery is better, but the energy density is lower; while in Example 2-10, the thickness of the first positive electrode active material layer and the thickness of the second positive electrode active material layer are thicker, and the energy density of the lithium ion battery is higher, but the cycle capacity retention rate is lower. It can be seen that controlling the thickness of the first positive electrode active material layer and the second positive electrode active material layer within the scope of this application can make the lithium ion battery have a higher energy density and a higher cycle capacity retention rate, and better stability.

[0074] Example 3-1~Example 3-2 The difference from Example 1-1 is that the type of positive electrode material is adjusted according to the parameters shown in Table 3. The performance test results of each embodiment and comparative example are shown in Table 3.

[0075] Table 3

[0076] It can be seen from Example 1-1, Example 3-1, and Example 3-2 that when the positive electrode material is nickel cobalt manganese oxide, lithium cobalt oxide, or a mixture of the two (the above ratio is a mass ratio), within the range of the compaction density and Formula I described in the present application, the lithium-ion battery can maintain a relatively high energy density and cycle capacity retention rate.

[0077] Example 4-1 to Example 4-3 The difference from Example 1-1 is that the coating conditions of the first positive electrode active material layer and the second positive electrode active material layer are adjusted according to Table 4, and the active materials are both lithium cobalt oxide. The performance test results of each embodiment and comparative example are shown in Table 4.

[0078] Table 4

[0079] By comparing Example 4-1 and Example 4-2, and Example 4-1 and Example 4-3 respectively, it can be seen that when the total thickness of the active material layer remains unchanged, the layered coating can further improve the cycle capacity retention rate of the lithium-ion battery.

[0080] Example 5-1 to Example 5-3 The difference from Example 1-1 is that the content and type of additives, as well as the relative content of adiponitrile (compound of Formula I) are adjusted according to the parameters shown in Table 5. The performance test results of each embodiment and comparative example are shown in Table 5.

[0081] Table 5

[0082] As can be seen from Table 5, the electrolyte includes the above-mentioned additives. When the type and mass content of the additives, and the mass content ratio of the additives to the compound of formula I are within the range described in the present application (the ratio of the above-mentioned additives is a mass ratio), the energy density and cycle capacity retention rate of the lithium ion battery are both high, achieving a balance between energy density and stability.

[0083] The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the principles of the present application should be included in the protection scope of the present application.

Claims

1. A secondary battery, characterized in that: The secondary battery comprises an electrolyte, an electrode assembly and a housing, wherein: The shell is made of steel; The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator. A plurality of the positive electrode sheets and a plurality of the negative electrode sheets are alternately stacked, and the separator is arranged between the positive electrode sheet and the negative electrode sheet, wherein: The positive electrode sheet includes a first positive electrode sheet and a second positive electrode sheet, and the compaction density of the first positive electrode sheet is Ag / cm 3 The compaction density of the second positive electrode sheet is B g / cm 3 , 3.3≤A≤4.3, 4.0≤B≤4.5, B>A; The electrolyte comprises a compound of formula I, wherein the compound of formula I contains a cyano group, and based on the mass of the electrolyte, the mass content of the compound of formula I is X%, 1≤X≤7.

2. The secondary battery according to claim 1, characterized in that: 3.5≤A≤4.2, 4.1≤B≤4.

4.

3. The secondary battery according to claim 1, characterized in that: 1.5≤X≤6。 4. The secondary battery according to claim 1, characterized in that: The first positive electrode plate comprises a first positive electrode current collector and a first positive electrode active material layer disposed on at least one surface of the first positive electrode current collector, the thickness of the first positive electrode active material layer is a μm, 25≤a≤90; and / or, The second positive electrode plate includes a second positive electrode current collector and a second positive electrode active material layer disposed on at least one surface of the second positive electrode current collector, and the thickness of the second positive electrode active material layer is b μm, 25≤b≤90.

5. The secondary battery according to claim 4, characterized in that: 30≤a≤75; and / or, 30≤b≤75.

6. The secondary battery according to claim 1, characterized in that: The compound of formula I includes at least one of the following compounds: Formula I-1, Formula I-2, Formula I-3, Formula I-4, Formula I-5, Formula I-6, Formula I-7, Formula I-8, Formula I-9.

7. The secondary battery according to claim 1, characterized in that: The positive electrode plate includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material includes at least one of lithium cobalt oxide and nickel cobalt manganese oxide.

8. The secondary battery according to claim 4, characterized in that: The first positive electrode active material layer includes a first material layer and a second material layer, and the first material layer is arranged between the first positive electrode current collector and the second material layer; and / or, the second positive electrode active material layer includes a third material layer and a fourth material layer, and the third material layer is arranged between the second positive electrode current collector and the fourth material layer; wherein, The thicknesses of the first material layer, the second material layer, the third material layer, and the fourth material layer are respectively a1 μm, a2 μm, b1 μm, and b2 μm, and: 15≤a1≤80; 10≤a2≤75; 15≤b1≤80; 10≤b2≤75。 9. The secondary battery according to claim 1, characterized in that: The electrolyte also includes at least one of the following additives: ethyl difluoroacetate, difluoroethyl acetate, ethyl monofluoroacetate, monofluoroethyl acetate, ethyl trifluoroacetate, trifluoroethyl acetate, methyl difluoroacetate, methyl monofluoroacetate, monofluoromethyl acetate, methyl trifluoroacetate, and propyl difluoroacetate; based on the mass of the electrolyte, the mass content of the additive is Y%, 10≤Y≤40, and 0.025≤X / Y≤0.

7.

10. An electronic device, characterized in that: The electronic device comprises the secondary battery according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A high-voltage electrolyte for a lithium ion battery and a lithium ion battery using the electrolyte

    CN109244529A

  • Electrolyte additive, electrolyte and secondary battery

    CN115548443A

  • Lithium ion battery and preparation method and application thereof

    CN115732747A

  • Positive pole piece and preparation method thereof, secondary battery, battery module, battery pack and power utilization device

    CN115832183A

  • Electrode assembly, battery cell, battery and electric device

    CN217606851U